Development of self-administered questionnaire on barriers, prescription practices, and guideline adherence of osteoporosis management among tertiary care clinicians: content validity and reliability analysis - Muhamad Jamil, Nur Khadijah; Mohamed, Isa Naina; Mokhtar, Sabarul Afian; Leong, Juzaily Fekry; Kamudin, Nur Azree Ferdaus; Muhammad, Norliza (Frontiers in Endocrinology, 2024)
Objective This study outlined the development of the barriers, prescribing practices, and guideline adherence for osteoporosis management according to the Clinicians' Osteoporosis Questionnaire (COQ) followed by an assessment of the content validity index and reliability test.The development of the COQ was performed in two stages. Stage I involved the development of the COQ questionnaire, and stage II involved judgmental evidence and quantification of the questionnaire. Five panel experts related to the study area and five clinicians participated in the validity of the COQ assessment. Fifty clinicians took part in the reliability test evaluation by filling out the questionnaire twice at two-week intervals. The content validity index (CVI) and content validity ratio (CVR) were analysed using Microsoft Excel, while Cohen's kappa statistic was used to determine the test-retest reliability using SPSS version 29.Forty items and three domains, namely, barriers, prescribing practices, and guideline adherence for osteoporosis management, were identified in the COQ (version 4.0). The scale-level CVI (S-CVI/Ave) for every domain was above 0.9, which is considered acceptable. The CVRs for all the items were above 0.7, except for two items in the barriers domain and two items in the guideline adherence domain. Two items were revised to improve the clarity of the item, and other items were retained based on consensus among the expert panel. Between the test and retest, the reliability of individual items ranged from moderate to almost perfect for the barrier domain (k = 0.42-0.86), prescribing practice domain (k = 0.79 to 0.87), and guideline adherence domain (k =0.46-1). None of the items had "fair" or "poor" agreement. Thus, the 40-item COQ (version 4.0) was finalized following the content and face validity analysis.Conclusions Through an iterative process, the development and assessment of the COQ showed a high degree of content validity and reliability in measuring the barriers, prescribing practices, and guideline adherence among clinicians managing osteoporosis. Future studies should aim to further validate this instrument across different populations and settings, as well as explore methods to enhance its reliability and validity.